Erythropoietin Reduces Death and Neurodevelopmental Impairment in Neonatal Hypoxic-Ischemic Encephalopathy - Seung Jun Bang; Juyoung Lee; Ga Won Jeon; Yong Hoon Jun (Korean Society of Neonatology, 2022)
Purpose Erythropoietin (EPO) is a promising neuroprotective drug. We investigated whether EPO has beneficial effects on neurodevelopmental outcomes in infants with hypoxic-ischemic encephalopathy (HIE). Methods We retrospectively reviewed the data of 56 infants with HIE born at or after 35 weeks of gestation who were admitted to Inha University Hospital between 2012 and 2021. Patients were divided into two groups based on EPO use and compared. In the EPO group, patients were administered 1,000 U/kg of EPO on days 1, 2, 3, 5, and 7, starting within 24 hours after birth. The primary outcome was death or neurodevelopmental impairment (NDI) at the age of 12 months. Results EPO was administered to 38 infants, and 18 did not receive EPO. Only 37.5% of patients with HIE (21/56) and 60% of patients with moderate-to-severe HIE (21/35) received therapeutic hypothermia. Among all patients with HIE, death or NDI (21.1 % vs. 50.0%; odds ratio [OR], 0.09; 95% confidence interval [CI], 0.01 to 0.78; P=0.029) and brain injury on imaging (42.1% vs. 83.3%; OR, 0.16; 95% CI, 0.03 to 0.92; P=0.040) were significantly lower in the EPO group than in the control group. Among patients with moderate-to-severe HIE, brain injury on imaging (54.2% vs. 90.9%; OR, 0.04; 95% CI, 0.002 to 0.700; P=0.027) was significantly lower in the EPO group than in the control group. Conclusion EPO administration significantly reduced mortality and NDI in infants with HIE. EPO can be considered an adjunctive therapeutic agent for neonatal HIE.